Analisis Implementasi Strategi Pengelolaan Cash Waqf Linked Sukuk Dalam Membangun Pemberdayaan Ekonomi Umat: Pendekatan Analytic Network Process (ANP) - Suratman Suratman; Suharto Suharto; Nasruddin Nasruddin (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2022)
Waqf has great potential to improve society’s welfare. Cash Waqf Linked Sukuk is one of the innovative instruments to develop waqf in Indonesia. Therefore, this study aims to develop a strategy for implementing CWLS management in supporting the economic development of the people in Indonesia. The Analytic Network Process (ANP) method with Super Decision Software is used in this study to identify problems, solutions, and management strategies for Cash Waqf Linked Sukuk (CWSL) in order to encourage economic empowerment of the people. The main challenges in dealing with Cash Waqf Linked Sukuk in Indonesia are regulatory issues, Sharia, trust, IT systems, and human resources. Sharia solutions, regulations, IT systems, trust, and HR solutions are all available to help manage CSWL. Transparency and accountability strategies, improving the quality of nazhir individuals and institutions, risk management, computerising waqf management, expanding socialisation of the benefits of Cash Waqf Sukuk, optimising investment and collaboration with stakeholders, collecting waqf through E-Waq, and the establishment of waqf educational institutions are some of the strategies that can be used to build the economic empowerment of the people in Indonesia